KAJIAN AWAL SIFAT OPTIS TAKLINIER BAHAN TRANSPARAN DALAM MEDAN LISTRIK STATIS - Prabowo, Krisno; Firdausi, K. Sofjan; Azam, Much. (BERKALA FISIKA, 2006)
In this paper, we study non linear optical characteristics of some transparency media in a static external electric field, E. The samples used in this experiment are mineral water, salt solution, and sugar solution. The optical characteristic investigated here is the change of polarization angle,b, of laser He-Ne after pass through the sample, against E. The strength of electric field is produced by high voltage (0-2000 volt) applied on two parallel plates (size 28 × 28 cm2). It is assumed that E inside the plates is homogeneous and fulfilled by relation of E = V/d. Results of experiment show that three samples have the tendency of b µ E in this experimental condition assumed to be optimal. For weak (mineral water) and strong (salt solution) electrolyte solution, we obtain a significant difference of gradient, that shows how dominant the electric dipoles in salt more than in mineral water. Other wise, change of b vs. E in sugar solution has only significant initial value of b. The tendency of b µ E is just only due to the contribution of dipoles of water molecules in sugar solution, since the sugar molecules is non polar.